2000
DOI: 10.1177/073346480001900405
|View full text |Cite
|
Sign up to set email alerts
|

Dr. Mom and Other Influences on Younger and Older Adults’ OTC Medication Purchases

Abstract: The present study examined age differences in the sources of information that older and younger adults use when making decisions about purchasing over-the-counter (OTC) cold/allergy medications. Participants completed a questionnaire addressing information sources that influence OTC purchases and advertising awareness. The questionnaire was given either before or after completing a decision task in which they searched a computerized display of label information and chose one of seven brand name medications to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Johnson and Drungle (2000) found that older adults were more likely to focus on active ingredients than were younger adults and were also more systematic in their information searches, presumably reflecting their greater experience with using these drugs. Stephens and Johnson (2000) also found that older adults were more likely to focus on side effects and drug interactions than were young adults. Such information is of obvious relevance to older adults, who are more likely than the young to be taking multiple prescription drugs at any one time.…”
Section: Impact Of Deliberative Decline On Judgments and Decisionsmentioning
confidence: 89%
“…Johnson and Drungle (2000) found that older adults were more likely to focus on active ingredients than were younger adults and were also more systematic in their information searches, presumably reflecting their greater experience with using these drugs. Stephens and Johnson (2000) also found that older adults were more likely to focus on side effects and drug interactions than were young adults. Such information is of obvious relevance to older adults, who are more likely than the young to be taking multiple prescription drugs at any one time.…”
Section: Impact Of Deliberative Decline On Judgments and Decisionsmentioning
confidence: 89%
“…For example, in examining decisions about over-the-counter drugs, Johnson and Drungle68 found that older adults were more likely to focus on active ingredients than were younger adults and were also more systematic in their information searches, presumably reflecting their greater experience with using these drugs. Stephens and Johnson106 also found that older adults were more likely to focus on side effects and drug interactions than were young adults. Such issues are most likely based on experiences and obviously relevant to older adults, who are more likely than the young to be taking multiple prescription drugs at any one time.…”
Section: The Impact Of Experience In Judgment and Decisionsmentioning
confidence: 96%
“…Hence, although there have been a few descriptive studies on consumers' information search behaviors regarding nonprescription drugs (Hughes, Whittlesea, and Luscombe 2002;Stephens and Johnson 2000), research comparing consumers' information search behaviors for prescription and nonprescription drugs has received little or no attention in the nonproprietary research literature, leaving a gap in the pharmaceutical advertising literature.…”
mentioning
confidence: 98%